A high-pressure pre-activation method for improving the stability of sodium-ion battery cathodes and applications thereof

CN122950667APending Publication Date: 2026-10-20HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611262821.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,在钠离子脱嵌过程中,此类材料容易发生钠离子与空位的有序化、晶格参数剧烈变化、过渡金属滑移以及复杂的相变

Benefits of technology

1、本发明通过在初始阶段采用高电压预活化,使部分晶格氧参与不可逆氧化反应,并诱导部分过渡金属离子迁移至钠层,从而将通常被认为不利的不可逆氧氧化和过渡金属迁移转化为可利用的结构稳定化过程,该方法对于钠电镍锰基/镍铁锰基层氧正极具有通用性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of layered oxide cathode materials for sodium-ion batteries, and particularly to a high-voltage pre-activation method and its application for improving the stability of sodium-ion battery cathodes. The method includes: assembling the layered sodium-ion battery cathode material into a battery, charging it to a first upper limit voltage V1 during the initialization stage, causing lattice oxygen in the cathode material to participate in an oxidation reaction, inducing some transition metal ions to migrate to the sodium layer and form interlayer pinning sites; after formation is completed, reducing the charging upper limit voltage to a second upper limit voltage V2 for cycling, where V1 > V2. This invention also provides a layered oxide cathode material with pillar ions in the sodium layer, having the chemical formula Na. x A y Ni a Fe b Mn c B d O2, A is a pillar ion such as Li, Mg, Ca, etc. This invention transforms the generally considered unfavorable irreversible oxidation and transition metal migration into a usable structural stabilization process, significantly improving the cycle stability and rate performance of layered sodium-ion battery cathode materials by constructing an interlayer pinning structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of layered oxide cathode materials for sodium-ion batteries, and specifically to a high-voltage pre-activation method and its application for improving the stability of sodium-ion battery cathodes. Background Technology

[0002] Layered transition metal oxides possess high theoretical specific capacity, relatively simple fabrication processes, and two-dimensional ion transport channels suitable for sodium ion migration, thus being considered promising cathode materials for sodium-ion batteries. Among these, nickel-manganese-based and nickel-iron-manganese-based layered oxides are relatively common cathode materials. However, during sodium ion insertion / extraction, these materials are prone to sodium ion and vacancy ordering, drastic changes in lattice parameters, transition metal slip, and complex phase transitions. These structural changes easily lead to stress accumulation during repeated cycling, further causing particle cracking, intensified polarization, and a decrease in reversible capacity.

[0003] It is generally believed that increasing the charging cutoff voltage of layered oxide cathodes will induce lattice oxygen to participate in charge compensation, which may be accompanied by oxygen loss, transition metal migration, and surface reconstruction. Therefore, existing technologies typically tend to suppress oxygen oxidation or suppress transition metal migration to improve cycle performance.

[0004] However, the inventors have discovered that for nickel-manganese-based / nickel-iron-manganese-based sodium electrode materials, increasing the charging cut-off voltage during the first cycle of formation and then reducing the charging cut-off voltage after activation can effectively improve the cycling performance of the material. Structural characterization results show that the high-voltage activation during the first cycle induces partial irreversible oxygen oxidation and induces the migration of some transition metal ions to the sodium layer. These migrating transition metal ions can form interlayer pinning sites, thereby inhibiting oxygen layer slip, drastic phase transitions, and structural collapse during subsequent cycles.

[0005] By introducing different pillar ions into the sodium layer, the oxygen oxidation under high voltage and its induced transition metal ion migration can be regulated, while the phase transition caused by the collapse of the layered structure under high voltage can be suppressed, thereby further enhancing the structural stabilization effect produced by high-voltage pre-activation. Therefore, it is necessary to provide a pre-activation method that utilizes, rather than completely suppresses, irreversible oxygen oxidation and transition metal migration under high voltage to construct a stable interlayer pinning structure during the initialization stage, thereby mitigating phase transitions, layer slip, and structural decay during subsequent cycling, and ultimately improving the cycle stability of the layered sodium-ion battery cathode material. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-voltage pre-activation method to improve the stability of the cathode of sodium-ion batteries. By using a voltage higher than the upper limit of subsequent cycles in the first or initial formation process, controlled oxygen oxidation and transition metal ion migration are induced to form an activated layered cathode material with high structural stability.

[0007] Another objective of this invention is to provide a layered oxide cathode material with different pillar ions in the sodium layer. By controlling oxygen oxidation under high pressure and its induced migration of transition metal ions, a stable interlayer pinning structure is constructed, thereby improving the structural stability and cycle performance of the material.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A high-voltage pre-activation method for improving the stability of the cathode in sodium-ion batteries includes the following steps: (1) Assemble the layered sodium-ion battery positive electrode material with the negative electrode, separator and electrolyte to form a sodium-ion electrochemical battery; (2) During the initialization stage, the battery is charged to the first upper limit voltage V1, so that the lattice oxygen in the positive electrode material participates in the oxidation reaction, and electrochemically induces some transition metal ions to migrate from the transition metal layer to the sodium layer, forming interlayer pinning sites in the sodium layer. (3) After the formation stage is completed, the upper limit voltage of the battery is reduced to the second upper limit voltage V2, and subsequent charge and discharge cycles are carried out. Where V1 > V2, V1 is a potential not lower than the onset potential of the oxygen oxidation reaction plateau, and V2 is a potential not higher than... The potential at which the oxidation reaction plateau begins.

[0009] Preferably, V1 is 4.3 to 4.6 VvsNa / Na+, and V2 is 3.9 to 4.1 VvsNa / Na+.

[0010] Preferably, the initialization stage includes one complete charge-discharge cycle or 2 to 5 consecutive charge-discharge cycles.

[0011] Preferably, the initialization stage has a charging rate of 0.1C.

[0012] This invention also provides a layered sodium-ion battery cathode material, wherein the chemical formula of the cathode material is Na. x A y Ni a Fe b Mn c B d O2, where 0.7≤x≤1, 0<y≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, and a+b+c+d=1; A is a sodium-layer pillar ion, selected from one or more of Li, Mg, Ca, K, Zn, and Sr; B is a transition metal layer doping element, selected from one or more of Li, Mg, Al, Ti, V, Cr, Cu, Zn, Zr, Nb, and Sn; After the positive electrode material is treated by the above-mentioned high-voltage pre-activation method, the sodium layer contains migrating transition metal ions, forming an interlayer pinning structure.

[0013] Preferably, when doping sites A and / or B contain two or more elements, the doping ratios of each element are the same or different.

[0014] Preferably, A is selected from a combination of Li and Ca, wherein the doping amount of Li is 0.02 to 0.04 and the doping amount of Ca is 0.02 to 0.04.

[0015] Preferably, the positive electrode material is an O3 phase layered oxide.

[0016] Preferably, the positive electrode material particles are hexagonal in shape and have a particle size of 2–6 μm.

[0017] This invention also provides a method for preparing the above-mentioned layered sodium-ion battery cathode material, comprising the following steps: (1) According to the stoichiometric ratio, the sodium source, nickel source, iron source, manganese source and the metal source corresponding to site A and site B are mixed and ball-milled with ethanol. (2) The product after ball milling is dried to obtain a precursor, and then calcined in air to obtain the layered sodium-ion battery cathode material.

[0018] Preferably, the sodium source is selected from one or more of sodium oxide, sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, and sodium oxalate; The nickel source, iron source, manganese source, and metal sources at sites A and B are each independently selected from one or more of the following: metal oxides, metal hydroxides, metal carbonates, metal acetates, metal nitrates, and metal oxalates.

[0019] Preferably, the ball-to-material ratio in the ball milling process is 5:1, the ball mill speed is 400 r / min, and the ball milling time is 3 h. The calcination temperature is 900℃ and the calcination time is 15h.

[0020] The present invention also provides the application of the above-mentioned layered sodium-ion battery cathode material in sodium-ion batteries.

[0021] The beneficial effects of this invention are: 1. This invention uses high-voltage pre-activation in the initial stage to allow some lattice oxygen to participate in irreversible oxidation reaction and induce some transition metal ions to migrate to the sodium layer, thereby transforming the generally unfavorable irreversible oxygen oxidation and transition metal migration into a usable structural stabilization process. This method is universal for sodium-based nickel-manganese / nickel-iron-manganese-based oxygen cathodes.

[0022] 2. By introducing different pillar ions into the sodium layer, this invention can regulate oxygen oxidation under high pressure and the migration of transition metal ions induced by it, and enable the pillar ions and the migrating transition metal ions to jointly construct a stable interlayer support structure, thereby further improving the structural stability and cycle performance of the material.

[0023] 3. This invention uses a higher upper limit charging voltage only in the initial formation stage. While achieving structural stabilization, it can reduce electrolyte decomposition, interfacial side reactions and oxygen loss caused by continuous high voltage operation. Moreover, this method is easy to combine with existing battery formation processes.

[0024] 4. In this invention, some sodium ions irreversibly released from the positive electrode during the high-voltage formation process can be used as an additional sodium source to compensate for the active sodium consumed during the negative electrode film formation and the first charge and discharge process, thereby improving the battery's first coulombic efficiency, reversible capacity and energy utilization rate. Attached Figure Description

[0025] Figure 1 The XRD pattern of the cathode material prepared using Example 1; Figure 2 These are scanning electron microscope (SEM) images of the cathode material prepared using Example 1; Figure 3 The charge-discharge curves of the battery prepared in Example 1 at a current density of 0.1C are shown. Figure 4 The charge-discharge curves of the battery prepared in Example 2 at a current density of 0.1C are shown. Figure 5 The graph shows the cycling performance of the batteries prepared using Example 1 and Comparative Example 1 at a current density of 1C. Figure 6 The graph shows the cycling performance of the batteries prepared using Examples 2, 7, and Comparative Example 2 at a current density of 1C. Figure 7 The graphs show the rate performance of the batteries prepared using Example 2 and Comparative Example 2 at different current densities. Figure 8 The image shows a scanning electron microscope (SEM) image of the positive electrode surface of the battery prepared using Comparative Example 1 after 300 cycles at 1C. Figure 9This is a scanning electron microscope image of the positive electrode surface of the battery prepared in Example 1 after 300 cycles at 1C. Detailed Implementation

[0026] The technical solutions in the embodiments of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0027] Example 1: A Na3 phase sodium-ion battery cathode material 0.91 Li 0.03 Ca 0.03 Ni 0.5 Mn 0.5 The pre-activation method for O2 includes the following steps: S1. Mix 23.89 mmol sodium carbonate, 25 mmol nickel oxide, 25 mmol manganese oxide, 0.79 mmol lithium carbonate and 1.5 mmol calcium carbonate, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0028] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0029] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2-4.0 V range.

[0030] Example 2: A NaNi phase sodium-ion battery cathode material 0.5 Mn 0.5 The pre-activation method for O2 includes the following steps: S1. Mix 26.25 mmol sodium carbonate, 25 mmol nickel oxide and 25 mmol manganese oxide, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0031] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0032] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2-4.0 V range.

[0033] Example 3: A Na3 phase sodium-ion battery cathode material 0.94 Li 0.06 Ni 0.5 Mn 0.5 The pre-activation method for O2 includes the following steps: S1. Mix 24.68 mmol sodium carbonate, 25 mmol nickel oxide, 25 mmol manganese oxide and 1.58 mmol lithium carbonate, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0034] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0035] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2-4.0 V range.

[0036] Example 4: A Na3 phase sodium-ion battery cathode material 0.88 Ca 0.06 Ni 0.5 Mn 0.5 The pre-activation method for O2 includes the following steps: S1. Mix 23.1 mmol sodium carbonate, 25 mmol nickel oxide, 25 mmol manganese oxide and 3 mmol calcium carbonate, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0037] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0038] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2-4.0 V range.

[0039] Example 5: NaNi, an O3-phase sodium-ion battery cathode material 1 / 3 Fe 1 / 3 Mn 1 / 3 The pre-activation method for O2 includes the following steps: S1. Mix 26.25 mmol sodium carbonate, 16.67 mmol nickel oxide, 16.67 mmol manganese oxide and 8.33 mmol iron oxide, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0040] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0041] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2-4.0 V range.

[0042] Example 6: A Na3 phase sodium-ion battery cathode material 0.94 Ca 0.03 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The pre-activation method for O2 includes the following steps: S1. Mix 26.25 mmol sodium carbonate, 16.67 mmol nickel oxide, 16.67 mmol manganese oxide, 8.33 mmol iron oxide and 1.5 mmol calcium carbonate, pour into a ball mill jar at a ball-to-material ratio of 5:1, add 10 ml ethanol, and ball mill at 400 r / min for 3 h.

[0043] S2. The ball-milled product is dried at 80°C to obtain precursor powder, which is then calcined at 900°C for 15 hours in air to obtain sodium-ion battery cathode material.

[0044] S3. The sodium half-cell assembled with this cathode material is cycled 3 times in the 2.0-4.4 V range, and then cycled at a current density of 1C in the 2.0-4.0 V range.

[0045] Example 7: NaNi, a cathode material for O3-phase sodium-ion batteries 0.5 Mn 0.5 The pre-activation method for O2 is basically the same as in Example 2, except that the number of formation cycles in S3 is changed to 1 cycle.

[0046] Example 8: A Na3 phase sodium-ion battery cathode material 0.91 Li 0.03 Ca 0.03 Ni 0.5 Mn 0.5 The pre-activation method for O2 is basically the same as in Example 1, except that the formation voltage in S3 is changed to 2.0-4.6V.

[0047] Comparative Example 1: Na, a cathode material for O3-phase sodium-ion batteries 0.91 Li 0.03 Ca 0.03 Ni 0.5 Mn 0.5The activation method of O2 is basically the same as that in Example 1, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0048] Comparative Example 2: NaNi, an O3-phase sodium-ion battery cathode material 0.5 Mn 0.5 The activation method of O2 is basically the same as that in Example 2, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0049] Comparative Example 3: Na, a cathode material for O3-phase sodium-ion batteries 0.94 Li 0.06 Ni 0.5 Mn 0.5 The activation method of O2 is basically the same as that in Example 3, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0050] Comparative Example 4: Na, a cathode material for O3-phase sodium-ion batteries 0.88 Ca 0.06 Ni 0.5 Mn 0.5 The activation method of O2 is basically the same as that in Example 4, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0051] Comparative Example 5: NaNi, an O3-phase sodium-ion battery cathode material 1 / 3 Fe 1 / 3 Mn 1 / 3 The activation method of O2 is basically the same as that in Example 1, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0052] Comparative Example 6: Na, a cathode material for O3-phase sodium-ion batteries 0.94 Ca 0.03 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The activation method of O2 is basically the same as that in Example 6, except that the formation voltage in S3 is changed to 2.0-4.0V.

[0053] Performance testing and results analysis: The electrochemical performance of sodium-ion batteries obtained by different formation methods in Examples 1-8 and Comparative Examples 1-6 was tested, and the results are as follows: Figure 1 The XRD pattern of the cathode material prepared in Example 1 shows that all characteristic diffraction peaks are clearly visible, and there are no redundant diffraction peaks, indicating that the cathode material is a pure O3 phase. Figure 2 The image shown is a scanning electron microscope image of Example 1, in which the particles are hexagonal in shape and have a particle size between 2 and 6 μm.

[0054] Figure 3 This is a charge-discharge curve of the battery prepared using Example 1 during the formation stage. Figure 4 The chart shows the charge-discharge curves of the battery prepared in Example 2 during the formation stage. A comparison reveals that, compared to formation at a lower cutoff voltage, a more pronounced oxygen oxidation reaction occurred in the first week of high-voltage formation, resulting in a larger irreversible capacity. This manifests as a decrease in coulombic efficiency in the first week. O-O dimerization and partial lattice oxygen precipitation may accompany the oxygen oxidation process, leading to the formation of oxygen vacancies in the material. This weakens the structural stability of transition metal ions at their original coordination positions and lowers the energy barrier for their migration from the transition metal layer to the sodium layer. Introducing pillar ions into the sodium layer did not significantly improve the reversibility of oxygen oxidation, but rather significantly suppressed the process. This indicates that the main role of pillar ions is not to directly improve the reversibility of the oxygen oxidation reaction, but rather to regulate the oxygen oxidation-induced migration of transition metal ions and subsequent structural reconstruction.

[0055] On the one hand, the pillar ions help to limit the disordered migration of transition metal ions, enabling some of the migrating ions to form stable interlayer pinning sites in the sodium layer; On the other hand, pillar ions can alleviate interlayer repulsion and lattice instability caused by excessive sodium removal under high voltage, thereby inhibiting layer slip and collapse of layered structures.

[0056] Therefore, the introduction of pillar ions can transform the irreversible structural changes induced by high voltage into a controlled reconstruction process that is conducive to the stability of subsequent cycles.

[0057] Figure 5 The graph shows the cycling performance of the batteries prepared using Example 1 and Comparative Example 1 at a current density of 1C. Figure 6 The graph shows the cycling performance of the batteries prepared using Examples 2, 7, and Comparative Example 2 at a current density of 1C.

[0058] The comparison shows that increasing the charging cutoff voltage during the formation stage can significantly improve the battery's cycle stability in the subsequent lower voltage range.

[0059] This stabilization effect mainly occurs during the first high-voltage formation process and can be observed in the formation voltage range of 4.3-4.6V. This indicates that high-voltage-induced oxygen oxidation and transition metal ion migration can promote favorable pre-reconfiguration of the cathode material and form stable interlayer pinning sites in the sodium layer.

[0060] Furthermore, the capacity retention of the material was further improved after the introduction of pillar ions, indicating that pillar ions can regulate ion migration and structural reconstruction during high-voltage formation and work together with transition metal ions that migrate to the sodium layer to stabilize the layered framework, thereby slowing down phase transition, layer slip and structural decay in subsequent cycles.

[0061] Figure 7 The graphs show the rate performance of the batteries prepared using Example 2 and Comparative Example 2 at different current densities. After high-voltage activation, the batteries can still maintain a high discharge capacity at higher current densities and exhibit good capacity recovery ability after the current density recovers. This indicates that high-voltage activation not only improves the cycle stability of the material, but also improves its rate performance and reaction kinetics.

[0062] High-voltage activation-induced controlled structural reconstruction optimizes sodium ion transport channels and reduces phase transition resistance and interfacial polarization during subsequent charge-discharge processes, thereby improving the electrochemical response capability of the material under rapid charge-discharge conditions.

[0063] like Figure 8 and Figure 9 As shown, comparing the scanning electron microscope images of the cathode surface of the batteries prepared in Comparative Example 1 and Example 1 after 300 cycles at 1C, it can be found that the cathode material in Example 1 still maintains a relatively complete particle morphology after long-term cycling, and no obvious microcrack propagation or structural breakage occurs inside the grains. This indicates that high-voltage activation can promote the formation of a more stable crystal framework, alleviate the local stress concentration generated during repeated sodium insertion / extraction, thereby inhibiting the initiation and propagation of microcracks and maintaining the integrity of the particle structure.

[0064] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-voltage pre-activation method for improving the stability of the positive electrode of a sodium-ion battery, characterized in that, Includes the following steps: (1) Assemble the layered sodium-ion battery positive electrode material with the negative electrode, separator and electrolyte to form a sodium-ion electrochemical battery; (2) During the initialization stage, the battery is charged to the first upper limit voltage V1, so that the lattice oxygen in the positive electrode material participates in the oxidation reaction, and electrochemically induces some transition metal ions to migrate from the transition metal layer to the sodium layer, forming interlayer pinning sites in the sodium layer. (3) After the formation stage is completed, the upper limit voltage of the battery is reduced to the second upper limit voltage V2, and subsequent charge and discharge cycles are carried out. Where V1 > V2, V1 is a potential not lower than the starting potential of the oxygen oxidation reaction plateau, and V2 is a potential not higher than the starting potential of the oxygen oxidation reaction plateau.

2. The high-pressure pre-activation method according to claim 1, characterized in that, The V1 is 4.3–4.6 Vvs Na / Na + The V2 is 3.9–4.1 VvsNa / Na + .

3. The high-pressure pre-activation method according to claim 1, characterized in that, The initialization phase includes one complete charge-discharge cycle or 2 to 5 consecutive charge-discharge cycles, with a charging rate of 0.1C.

4. The high-pressure pre-activation method according to claim 1, characterized in that, The chemical formula of the layered sodium-ion battery cathode material is Na. x A y Ni a Fe b Mn c B d O2, where 0.7≤x≤1, 0≤y≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, and a+b+c+d=1; A is a sodium-supported ion, selected from one or more of Li, Mg, Ca, K, Zn, and Sr; B is a transition metal layer doping element, selected from one or more of Li, Mg, Al, Ti, V, Cr, Cu, Zn, Zr, Nb, and Sn.

5. A layered sodium-ion battery cathode material, characterized in that, The chemical formula of the positive electrode material is Na. x A y Ni a Fe b Mn c B d O2, where 0.7≤x≤1, 0<y≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, a+b+c+d=1; A is the sodium layer pillar ion, selected from one or more of Li, Mg, Ca, K, Zn, and Sr; B is the transition metal layer dopant element, selected from one or more of Li, Mg, Al, Ti, V, Cr, Cu, Zn, Zr, Nb, and Sn. After the cathode material is treated by the high-voltage pre-activation method according to any one of claims 1 to 3, the sodium layer contains migrating transition metal ions, forming an interlayer pinning structure.

6. The layered sodium-ion battery cathode material according to claim 5, characterized in that, The A is selected from a combination of Li and Ca, wherein the doping amount of Li is 0.02 to 0.04 and the doping amount of Ca is 0.02 to 0.

04.

7. The layered sodium-ion battery cathode material according to claim 5, characterized in that, The cathode material is an O3 phase layered oxide.

8. A method for preparing the layered sodium-ion battery cathode material according to claim 5, characterized in that, Includes the following steps: (1) According to the stoichiometric ratio, the sodium source, nickel source, iron source, manganese source and the metal source corresponding to site A and site B are mixed and ball-milled with ethanol. (2) The product after ball milling is dried to obtain a precursor, and then calcined in air to obtain the layered sodium-ion battery cathode material.

9. The preparation method according to claim 8, characterized in that, The sodium source is selected from one or more of sodium oxide, sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, and sodium oxalate; The nickel source, iron source, manganese source, and metal sources at sites A and B are each independently selected from one or more of the following: metal oxides, metal hydroxides, metal carbonates, metal acetates, metal nitrates, and metal oxalates. The ball-to-material ratio in the ball milling process is 5:1, the ball mill speed is 400 r / min, and the ball milling time is 3 h. The calcination temperature is 900℃ and the calcination time is 15h.

10. The application of the layered sodium-ion battery cathode material according to claim 5 in a sodium-ion battery.